Effect of maximal mental effort during elastic band training on neuromuscular adaptations in older women - Harper, Lacey; Anderson, Kayla; Reed, William; Buford, Kaden; Acosta, Anna; Grazer, Jacob; Buresh, Robert; Martin, Tim; Hester, Garrett (Frontiers in Aging, 2025)
IntroductionNeural impairments contribute to age-related weakness, yet strategies complementing practical exercise training to target neuromuscular adaptations are lacking.ObjectiveThis study aimed to determine if combining maximal mental effort (MME) with elastic band training (EBT) augments neuromuscular adaptions in older women.MethodsUntrained older women (71 ± 4 years) were randomly assigned to EBT (n = 11), EBT + MME (n = 13), or a control (CON; n = 10) group. EBT and EBT + MME performed 6 weeks of moderate-intensity, total body elastic band training, but EBT + MME imagined a maximal muscle contraction during each exercise. Neuromuscular outcomes including voluntary activation (VA), contractile properties, dynamic strength (1-repetition maximum; 1-RM), and isometric peak torque of the elbow flexors (EF) and knee extensors (KE) were assessed. Additionally, KE and EF cross-sectional area (CSA) and muscle quality were captured, as well as lean mass. Two-way mixed ANOVAs were used to compare groups across time.ResultsVA (p = 0.182) and contractile properties (p > 0.05 for all) remained unchanged. Compared to CON, 1-RM (p = 0.004), KE peak torque (p = 0.034), CSA (p < 0.001 for both), and muscle quality (p = 0.001–0.021) improved in EBT and EBT + MME, but no differences existed between these groups (p > 0.05). Lean mass remained unchanged (p = 0.481–0.753).ConclusionCompared to EBT, MME did not result in augmented strength or VA. Future research is needed in sarcopenic or older adults suffering from greater age-related weakness. Despite the short training duration, positive effects of home-based, EBT were found for muscle size, quality, and strength in older women. The promotion of accessible forms of resistance training for older adults, such as EBT, is warranted.